A revision of the genus Herminella Spaeth (Chrysomelidae: Cassidinae: Notosacanthini), with a description of a new related genus and species from Madagascar - Borowiec, Lech; Wietojañska, Jolanta (Zootaxa, 2014)
The genus Herminella Spaeth from southern Africa is revised. It comprises four species: Herminella liliputana Spaeth and H. marshalli Spaeth are redescribed and two species are described as new—H. quadrimaculata from South Africa and H. flavocostata from Nambia and South Africa. A new related genus and species Hermosacantha madagascarica from Madagascar is described. Members of both genera belong to the smallest world cassids.